Unveiling the Romance Scam Scheme: Psychological Manipulation and Its Impact on Victims - Yosiandra, Syakira Yuniar; Sakariah, Dewi Saraswati (Faculty of Humanities, Diponegoro University, 2024)
This study aims to analyze the schemes used by Romance Scam perpetrators to manipulate victims, which ultimately leads to psychological and financial impacts on the victims. The analysis applies the Dramaturgy concept and Psychological Manipulation theory, which are relevant in understanding the interaction patterns between perpetrators and victims. This research is a literature review, with data collected from secondary sources, including Japanese online news portals such as Ameblo and Newspostseven, as well as social media platforms like Instagram. The Dramaturgy concept is used to explain identity falsification and the avoidance of direct communication by the perpetrators, while the Psychological Manipulation theory is applied to examine exaggerated expressions of love and requests for money by the perpetrators. These schemes significantly impact victims both psychologically and financially, often leaving long-lasting effects on their mental well-being and economic stability, indicating the extent of significant psychological and financial impacts on the victims. This research is to enrich the literature on cybercrime in Japan, particularly focusing on the emotional and relational aspects in the context of fraud.